Mild Cognitive Impairment and driving: Does in-vehicle distraction affect driving performance?. (June 2017) - Beratis, Ion N.; Pavlou, Dimosthenis; Papadimitriou, Eleonora; Andronas, Nikolaos; Kontaxopoulou, Dionysia; Fragkiadaki, Stella; Yannis, George; Papageorgiou, Sokratis G.
Highlights: In-vehicle distraction was evaluated in MCI patients and cognitively intact drivers. Conversing with passenger and mobile phone use were the two distraction conditions. MCI drivers had a greater increase of reaction time in the mobile-phone condition. MCI drivers had a marked increase of accident risk in the mobile-phone condition. Mobile phone may have a detrimental impact on driving performance of MCI patients. Abstract: Objectives: In-vehicle distraction is considered to be an important cause of road accidents. Drivers with Mild Cognitive Impairment (MCI), because of their attenuated cognitive resources, may be vulnerable to the effects of distraction; however, previous relevant research is lacking. The main objective of the current study was to explore the effect of in-vehicle distraction on the driving performance of MCI patients, by assessing their reaction time at unexpected incidents and accident probability. Methods: Thirteen patients with MCI (age: 64.5 ± 7.2) and 12 cognitively intact individuals (age: 60.0 ± 7.7), all active drivers were introduced in the study. The driving simulator experiment included three distraction conditions: (a) undistracted driving, (b) conversing with passenger and (c) conversing through a hand-held mobile phone. Results: The mixed ANOVA models revealed a greater effect of distraction on MCI patients. Specifically, the use of mobile phone induced a more pronounced impact on reaction time and accident probability in the group of patients, as compared to healthy controls. On the other hand, in the driving condition "conversing with passenger" the interaction effects regarding reaction time and accident probability were not significant. Notably, the aforementioned findings concerning the MCI patients in the case of the mobile phone were observed despite the effort of the drivers to apply a compensatory strategy by reducing significantly their speed in this driving condition. Conclusion: Overall, the current findings indicate, for the first time, that a common driving practice, such as the use of mobile phone, may have a detrimental impact on the driving performance of individuals with MCI.